Performance Analysis of the Fast Platform Supply Vessel with a Conventional V-Hull Shape with the Addition of a Chine and a Different Bow Using Computational Fluid Dynamics Method - Rumapea, Fedrik Immanuel; Bahatmaka, Aldias; Hamizan, Banin; Rahardian, Pramudya; Rantisi, Umar Zaid; Kurniaputri, Dias Fitria (Mekanika: Majalah Ilmiah Mekanika, 2026)
Indonesia is the largest country in Southeast Asia, consisting of more than 17,000 islands and a coastline of approximately 81,000 kilometers, with over half of its territory covered by water. To optimize this vast marine potential for public welfare, comprehensive data collection and mapping are essential. The oil and gas sector remains a key contributor to national revenue. For instance, Pertamina Hulu East Kalimantan (PHKT) exceeded its 2023 production target, achieving around 9,900 barrels of oil and 45 million cubic feet of gas per day. To support offshore operations, a Platform Supply Vessel (PSV) prototype named Bramantya was designed. This study analyzes the vessel using Computational Fluid Dynamics (CFD) to determine the optimal hull form for operational performance and fuel efficiency. Three hull variations were examined: a conventional hull, a hull with additional chines, and a wide-bow hull. The simulation was validated against previous experimental studies, showing consistent linear results with an average error of 4.25%. Simulations at Froude numbers 0.2–0.6 show that the wide downward-bowed hull reduces drag by 7.69% compared to the conventional hull, thereby improving fuel efficiency.